Quality : a critical introduction - Beckford, John, 1958- (Routledge, Taylor & Francis Group, 2017)
Exploring the basics of management theory and the work of the quality gurus, who have formed the foundation of current practice, this new edition builds upon the previous editions' unique critical perspective of quality. A number of key management practices are considered including the new ISO9001:2015 standards, EFQM, systems thinking, systems practice, business process reengineering, six-sigma, organisational learning, intelligent organisation, skills based quality management and service quality management. An extended, in-depth case studies completes the text, exploring organisational performance transformation through the use of key methodologies, such as: soft systems; viable systems modelling; process analysis, job design and statistical methods -- Provided by publisher.